Biochemical Characterization of a New Oligoalginate Lyase and Its Biotechnological Application in Laminaria japonica Degradation - Li, Shangyong; Wang, Linna; Jung, Samil; Lee, Beom Suk; He, Ningning; Lee, Myeong-Sok (Frontiers in Microbiology, 2020)
Oligoalginate lyases catalyze the degradation of alginate polymers and oligomers into monomers, a prerequisite for biotechnological utilizing alginate. In this study, we report the cloning, expression and biochemical characterization of a new polysaccharide lyase (PL) family 17 oligoalginate lyase, OalV17, from the marine bacterium Vibrio sp. SY01. The recombinant OalV17 showed metal ion independent and detergent resistant properties. Furthermore, OalV17 is an exo-type enzyme that yields alginate monomers as the main product and recognizes alginate disaccharides as the minimal substrate. Site-directed mutagenesis followed by kinetic analysis indicates that the residue Arg231 plays a key role in substrate specificity. Furthermore, a rapid and efficient alginate monomer-producing method was developed directly from Laminaria japonica. These results suggest that OalV17 is a potential candidate for saccharification of alginate.